GREEN ENERGY LITERACY: A REVIEW AND BIBLIOMETRIC ANALYSIS - Iman Gudiman; Irvan Permana; Didit Ardianto (Universitas Lambung Mangkurat, 2023)
Research on the importance of energy literacy has increased, this can be seen from the many articles that have been studied on this theme. Increased attention to the importance of energy literacy is related to the influence of the quality of energy literacy of citizens of a country which directly impacts the good or bad quality of the environment due to climate change. This study aims to evaluate the most relevant themes related to Energy Literacy based on bibliometric analysis, with input using the keywords